BIOACCUMULATION OF HEAVY METALS IN FISHES (CATLA CATLA AND TILAPIA MOZAMBIQUE) OF LAKSHMINARAYANA LAKE, EDULABAD, HYDERABAD, TELANGANA - B. Prameela, B. Jyothi (Chelonian Research Foundation, 2024)
Heavy metals such as lead (Pb), cadmium (Cd), mercury (Hg), and arsenic (As) are persistent environmental pollutants. Unlike organic pollutants, heavy metals are non-biodegradable and can accumulate in aquatic ecosystems, leading to long-term ecological consequences (Shahjahan et al., 2022). These metals can enter water bodies through various pathways, including industrial effluents, agricultural runoff, and atmospheric deposition. Once in the aquatic environment, heavy metals can be taken up by aquatic organisms, leading to bioaccumulation and biomagnification through the food chain (Hayati et al., 2017). Fish are particularly susceptible to heavy metal contamination due to their position in the aquatic food web. They can accumulate heavy metals in their tissues, including muscle, liver, and gills, which can have detrimental effects on their health and survival (Suhendrayatna et al., 2002). Catla catla and Tilapia mozambique are two fish species commonly found in Lakshminarayana Lake. These species are important not only for their ecological roles but also for their economic value as a source of food for local communities. Catla catla is commonly known as the Indian carp or catla fish, is a freshwater species native to the Indian subcontinent. Its robust, elongated body features a slightly convex dorsal profile, and its coloration ranges from silver to light gray. Notably, the head lacks scales, and the mouth is large and upturned, adapted for surface feeding (Avigliano et al., 2019). Barbels near the mouth aid in sensory perception. The dorsal fin displays a distinct black margin. Ecologically, Catla catla plays a vital role as an herbivorous filter feeder, consuming phytoplankton, algae, and detritus. However, its significance extends beyond ecological dynamics. Tilapia is scientifically known as Oreochromis mossambicus, is a freshwater fish species native to southeastern Africa and Asia. Its robust, elongated body features a slightly compressed shape. The coloration of Tilapia mozambique varies, ranging from silvery-gray to olive-brown. Ecologically, Tilapia mozambique plays a vital role as an herbivorous filter feeder, consuming phytoplankton, algae, and detritus. However, its significance extends beyond ecological dynamics (Virk et al., 2003). Bioaccumulated heavy metals pose health risks to both the fish and humans who consume them. Chronic exposure may lead to organ damage, impaired growth, reproductive issues, and compromised immune function. Monitoring Tilapia mozambique helps evaluate environmental pollution and potential human health hazards, emphasizing the delicate balance between aquatic ecosystems and our well-being. Chronic exposure may lead to organ damage, impaired growth, reproductive issues, and compromised immune function (El Shafei et al., 2016). Monitoring Catla catla helps evaluate environmental pollution and potential human health hazards, emphasizing the delicate balance between aquatic ecosystems and our well-being. Understanding the levels of heavy metals in Lakshminarayana Lake and their accumulation in fish tissues is crucial for evaluating the ecological health of the lake and the safety of fish consumption for local communities. This research will contribute to the development of effective management strategies to mitigate heavy metal pollution, protect aquatic life, and safeguard human health. While heavy metal contamination in fish is a well-documented phenomenon, this study is unique in its focus on the specific fish species prevalent in Lakshminarayana Lake—Catla catla and Tilapia mozambique. By analyzing heavy metal concentrations in the muscle, liver, and gill tissues of these species, the research offers a detailed view of bioaccumulation patterns that has not been previously explored in this context.